PENERAPAN METODE ANALYTICAL HIERARCHY PROCESS PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN JENIS PRODUK SOUVENIR PERNIKAHAN YANG DIMINATI KONSUMEN BERBASIS WEB DI UMKM TAZKIYA SOUVENIR - Asqarini, Putu Luvi; Kustanto, Kustanto; Susyanto, Teguh (STMIK Sinar Nusantara, 2024)
ABSTRACTTazkiya Souvenir is a wedding souvenir manufacturer that produces various kinds of wedding souvenir products. The purpose of this research is to develop a long process with the help of a decision support system to determine the selection of souvenir products to be purchased, with the results adjusted based on the number of criteria and ranking arrangements from the highest to the lowest. . This study uses the Analytical Hierarchy Process (AHP) method because this method determines the level of importance of each criterion and is followed by a final ranking process. The result of this research is the creation of a decision support system application that can help the process of selecting the type of wedding souvenir product that suits consumer interests based on the highest value ranking results. Based on the calculation process using the Analytical Hierarchy Process method, the first place is Wallet Fold (0.325), the second place is occupied by a Fan (0.304), the third place is a Blacu Bag (0.213) and in the last position is a Pouch (0.156). Tests in this study use functionality testing which is useful for knowing the software can function properly and the system is as expected. Then a validity test was carried out using the McCall method to get a calculation result of 77.8% which is included in the good category. Keywords: Decision Support System, Wedding Souvenir, AHP